Słownictwo czynności śledczych w języku rosyjskim XI–XVII wieku - Czaszczyna, Elena (Studia Rossica Posnaniensia, 2017)
Investigative action is understood here as research into the circumstances of a case and establishing the truth. During the history of Russian legislation, the ways of gathering and submitting proof were changed. The article looks at the juridical lexicon of texts, which show these processes from the period of Ancient Russia to the late 17th century.